The Effect of Inter-Personal Communication and Perception of Leadership Quality on Employee's Satisfaction in Regional Office of Religion Ministry of North Sumatera - Rahayu Sri Utami; Candra Wijaya; Mardianto Mardianto (BIRCU, 2019)
Job satisfaction is one of the important factors to get optimal work results through communication, perception and satisfaction of employees in the office. So, the aim of this paper is to know the impact of inter-personal communication and perception of leadership quality on employee’s satisfaction in the office of the region of the ministry of religion in North Sumatera Province. This research was conducted in the Regional Office of the Ministry of Religion, North Sumatra Province. This research is planned to take place for three months from July to September 2018. This type of research is quantitative research with the research method used is a study of the description of correlative studies. The result is Interpersonal communication has an influence on the work satisfaction of environmental employees of the Ministry of Religion Regional Office of North Sumatra Province at 13.8%. This finding means that employee job satisfaction can be predicted through interpersonal communication.